2021
DOI: 10.1145/3477604
|View full text |Cite
|
Sign up to set email alerts
|

Building Cultural Heritage Reference Collections from Social Media through Pooling Strategies: The Case of 2020’s Tensions Over Race and Heritage

Abstract: Social networks constitute a valuable source for documenting heritage constitution processes or obtaining a real-time snapshot of a cultural heritage research topic. Many heritage researchers use social networks as a social thermometer to study these processes, creating, for this purpose, collections that constitute born-digital archives potentially reusable, searchable, and of interest to other researchers or citizens. However, retrieval and archiving techniques used in social networks within heritage studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Thus, selecting a hybrid classification approach on social data totally depends upon the dataset and the problem being investigated (Miao et al, 2009). Similarly, research has suggested a few approaches devised around the concept of pooling wherein the selected documents from the given dataset are annotated with relevant concepts by the human experts to create a document collection (pool) of relevant documents for future referencing, reuse, and other information retrieval related tasks (Aslam et al, 2003;Losada et al, 2017;Otero et al, 2021). This implies that once a pool of relevant documents is collected, a machine-learning algorithm can be used to annotate future documents.…”
Section: Hybrid Text Classification Approachesmentioning
confidence: 99%
“…Thus, selecting a hybrid classification approach on social data totally depends upon the dataset and the problem being investigated (Miao et al, 2009). Similarly, research has suggested a few approaches devised around the concept of pooling wherein the selected documents from the given dataset are annotated with relevant concepts by the human experts to create a document collection (pool) of relevant documents for future referencing, reuse, and other information retrieval related tasks (Aslam et al, 2003;Losada et al, 2017;Otero et al, 2021). This implies that once a pool of relevant documents is collected, a machine-learning algorithm can be used to annotate future documents.…”
Section: Hybrid Text Classification Approachesmentioning
confidence: 99%